Succession of the sessile benthic community at a coral reef restoration site - Chomitz Ray, Benjamin (2023)
Introduction: Ecosystem restoration facilitates ecological succession. When a coral reef experiences a disturbance, the community of sessile benthic organisms can follow a successional trajectory that favors the dominance of coral or a change of state to an ecosystem dominated by algae. Objective: To better understand the impact of coral transplants on succession of the sessile benthic community. Methods: To measure and monitor the coral cover (cm2) of Pocillopora spp., and the composition of the associated benthic community, experimental and control coral reef patches were established at the coral restoration site in Golfo Dulce, South Pacific Costa Rica. Thirty Pocillopora spp. colonies were attached to nails on the substrate in an experimental patch. The control coral patch contained nails with non-transplanted colonies. Both treatments were photographed monthly during a period of eight months. Changes in the coverage of coral and other sessile benthic organisms were measured from the images and compared over time between the experimental and control patches. Results: The coral transplants experienced bleaching events in August through September 2019 and January through February 2020. The first bleaching event possibly due to sedimentation, and the second to high temperatures. By the end of the experiment, 83 % of the colonies had survived. The live colonies grew significantly following transplantation; > 67 % of their initial coverage area after eight months. In the experimental patch, the areas of Pocillopora spp., coralline crustose algae (CCA), and cyanobacteria increased while the area of algal turf decreased. The increase in coral coverage and CCA, and decrease in algal turf in the experimental patch could be due to herbivores attracted to transplants. The increase in cyanobacteria in the experimental patch could be the result of higher temperatures and may have been a factor in the death of colonies.Conclusions: The transplantation of Pocillopora spp. colonies in Golfo Dulce changed the early successional trajectory of the sessile benthic community to favor the dominance of coral dominance in the experimental patch. These results may be useful in informing expectations for future restoration efforts.